Didactic principles of guiding preschool children to inventiveness - Rustamova Gulmira Yoryigit kizi (Genius Publishing Group, 2022)
This article is devoted to the use of TRIZ technology techniques in teaching and upbringing preschool children. TRIZ technology allows us to teach and train a creative child. The purpose of using this technology in kindergarten is, on the one hand, the development of such qualities of thinking as flexibility, mobility, consistency; on the other hand, search activity, the desire for innovation; the development of speech and creative imagination. The article notes that TRIZ significantly contributes to the formation of mathematical imagination, allows children to develop their thinking, mathematical abilities by solving creative problems. Today, TRIZ pedagogy is already widely used in practice in the education system of developed countries of the world
Keywords: Preschool education, preschool age, personality, TRIZ pedagogy, theory of inventive problem solving, level of preparation for school, creativity, creativity, mathematical education